Residual Periodontal Ligament in Extracted Teeth - Is It Associated With Indication for Extraction? - Juliana Maier; Camila Silveira Sfreddo; Ana Paula Pereira Reiniger; Karla Zanini Kantorski; Ulf ME Wikesjö; Carlos Heitor Cunha Moreira (Elsevier, 2021)
Background: Periodontal disease is a major cause of tooth loss. Few studies have evaluated the residual area of the periodontal ligament in extracted teeth and, to the best of our knowledge, none from Latin America have done so regarding indications for extraction. The aim of this study was to evaluate the residual periodontal ligament (RPL) with respect to indication for extraction in a sample of teeth from a Brazilian Public Health Service district. Materials and methods: All teeth extracted within the Public Health Service district of Santa Maria, Brazil, over a 5-month period were requested for analysis. A total of 414 teeth eligible for measurement were stained and evaluated for RPL using a stereo microscope. Participating Public Health Service dentists completed a questionnaire detailing demographic variables and indication for each extracted tooth. The percentage of RPL was determined for each tooth. Comparisons of RPL between teeth extracted on periodontal versus other indications were made using the Mann-Whitney test. Results: RPL averaged 34.8% for teeth extracted on periodontal indications versus 79.5% for other teeth (P ≤ 0.001). When considering teeth with an RPL ≥ 30% as possible to maintain, 189 (76%) of the teeth extracted on periodontal indications could have been maintained. When RPL cut-off limits of ≥ 40% or ≥ 50% are applied, 93 (37%) and 43 (17%) teeth, respectively, could have been maintained. Conclusion: This study suggests that strictly based on RPL, a large number of teeth extracted on periodontal indications conceivably could be maintained.